Análise da morfagem de winglets utilizando ligas com memória de forma - Silva, Raphael Santana (2018)
The use of shape memory alloys (SMA) as actuators allows to build adaptive structures and to develop the concept of morphing. In the aeronautical industry, the morphing of aircraft is inspired by the flight of birds, as for the flaps and ailerons. Nowadays, the wing tips may have a static device called winglet that has an important aerodynamic function in cruise flight, but generates lift losses during take-off and landing. This work aims to analyze the winglet’s morphing using SMAs actuators. Two alternative models in bias configuration are presented: spring-pulley system and torsion springs system. Both models aim to represent conditions for application of a smallscale wing. This study shows a proof of concept and designs two prototypes for experimental verifications. Several parametric investigations evaluate the influence of air flow speed and the sensitivity of SMA wire diameter and spring index. The results show the conditions to obtain the desired geometric variation of the winglet and the feasibility of the actuation using SMA springs.